The Mark, the Thing, and the Object: On What Commands Repetition in Freud and Lacan - Van de Vijver, Gertrudis; Bazan, Ariane; Detandt, Sandrine (Frontiers in Psychology, 2017)
In Logique du Fantasme, Lacan argues that the compulsion to repeat does not obey the same discharge logic as homeostatic processes. Repetition installs a realm that is categorically different from the one related to homeostatic pleasure seeking, a properly subjective one, one in which the mark “stands for”, “takes the place of”, what we have ventured to call “an event”, and what only in the movement of return, in what Lacan calls a “thinking of repetition”, confirms and ever reconfirms this point of no return, which is also a qualitative cut and a structural loss. The kind of “standing for” Lacan intends here with the concept of repetition is certainly not something like an image or a faithful description. No, what Lacan wishes to stress is that this mark is situated at another level, at another place, it is “entstellt”, and as such, it is punctually impinging upon the bodily dynamics without rendering the event point by point, without having an external meta-point of view, but cutting across registers according to a logics that is not the homeostatic memory logics. This paper elaborates on this distinction on the basis of a confrontation with what Freud says about the pleasure principle and its beyond in Beyond the Pleasure Principle, and also takes inspiration from Freud’s Project for a Scientific Psychology. We argue that Lacan’s theory of enjoyment takes up and generalizes what Freud was after in Beyond the Pleasure Principle with the Wiederholungszwang, and pushes Freud’s thoughts to a more articulated point: to the point where a subject is considered to speak only when it has allowed the other, through discourse, to have impacted and cut into his bodily pleasure dynamics.